The Effect of Problem Based Learning Model on the Ability of Class V Mathematics Problem Solving SDN JATI SIDOARJO: Pengaruh Model Pembelajaran Berbasis Masalah Terhadap Kemampuan Pemecahan Masalah Matematika Kelas V SDN JATI SIDOARJO - Avisha Heraspin; Rifki Afandi (Universitas Muhammadiyah Sidoarjo, 2020)
The study aims to describe the influence of the application of problem-based learning models to mathematical problem solving abilities of fifth grade students of SDN Jati Sidoarjo. Describe how much influence the implementation of problem-based learning models on mathematical problem solving abilities of fifth grade students of SD Sido Jati SDN. This study uses a quantitative approach. The research design uses True Experimental Designs in the type of Posttest Only Control Design. The population that was used as the object of research was all students of grade V Jati Sidoarjo Elementary School totaling 44 students, the sampling technique in this study used Simple Random Sampling which was carried out in class V of SD Sido Jati as many as 22 experimental class students and 22 control class students. The results showed 1) there was an effect on problem solving abilities of fifth grade students of Jati SDN by using problem-based learning models and obtained results of tcount = 2.107 greater than t table = 2.08 (2.107> 2.08) with a significance level of 5%. 2) there is a moderate influence between the problem-based learning model on the mathematical problem-solving ability of class V SDN Jati Sidoarjo. It is evident from the calculation of the data using the Eta Squared formula obtained a value of 0.096. If interpreted then 0.06 ≤ 0.096 <0.14, which is concluded to have a moderate influence.